Spotify: From music streaming start-up to global audio company - Stefan Schmid; Tobias Romey (ESCP Europe Wirtschaftshochschule Berlin, 2022)
During the last few decades, the internet and digital technology have fundamentally changed the global music industry. As a consequence, new companies and novel business models have emerged. Spotify, one of the new players in the music industry, has expanded its business activities and grown to become the leading streaming company worldwide. Today, Spotify offers a wide variety of audio products, such as podcasts and audiobooks, to subscribers, as well as significant service solutions for artists and music producers alike. This case study describes the development of the music industry before the advent of Spotify. After presenting Spotify's origins and after discussing Spotify's market entry into the most important music market in the world, namely, the US, the case study focuses on the company's growth. We show that acquisitions of other companies enabled Spotify to develop its services further, as well as to diversify its product portfolio. We also shed light on Spotify's internationalization as another important driver of firm growth. Over time, Spotify's relationship with major labels has changed, and this case study reveals how Spotify has gained power while getting more independent from the major labels.
urn:nbn:de:101:1-2022091415203740988630
Keywords: A20; A23; L13; L21; L25; L82; M10; M13; M16; 650; Acquisitions; Case Study; Diversification; Internationalization; Digital Music; Firm Growth; Internet; Music Label; Market Entry; Music Industry; Platform; Podcast; Product Development; Spotify; Streaming